DEVELOPMENT OF LITERACY IN PRIMARY SCHOOL STUDENTS BASED ON MULTIMEDIA TOOLS - Embergenova Gulsara (Web of Journals Publishing, 2026)
This article highlights the importance of multimedia tools in developing literacy in primary school students, their impact on the educational process, and ways to implement them effectively. The advantages of multimedia resources and practical experience in their application in educational conditions are also analyzed.
Keywords: Primary education, literacy, multimedia tools, interactive methods, learning activities.